Stamping Out Automatons ; Gatekeeping: The Mix of Topics and Selection of Stories - Mary Paulsell; Richard P. Carlson (Journal of Applied Communications, 1986)
Review of " Stamping Out Automatons," by Maria Raden ; "Gatekeeping: The Mix of Topics and Selection of Stories," by Guido H. Stempel III.